Michael Marinov memorial volume - Olshanetsky, Mikhail
Includes bibliographical references.; This book is dedicated to the memory of Michael Marinov, the theorist who, together with Felix Berezin, introduced the classical description of spin by anticommuting Grassmann variables. It contains original papers and reviews by physicists and mathematicians written specifically for the book. These articles reflect the current status and recent developments in the areas of Marinov's research: quantum tunneling, quantization of constrained systems, supersymmetry, and others. The personal recollections included portray the human face of M Marinov, a person of great knowledge and integrity.